In Augustinum: Maximinus of Durostorum and his dispute with Augustine (Research Announcements "Heritage BG", 2025)
The publication presents one day of the life of Maximinus of Durostorum, mainly his public dispute with Augustine of Hippo. A comparison is made between the two bishops and the available information about Maximinus of Durostorum has been analyzed. Neglected for a long time, the bishop of Durostorum appears as a well-educated leader with authority and erudition not only to face one of the greatest theologians of the Christian world but to dominate the verbal encounter. As a result, we contributed to the image of the Arian bishops from the Balkans, revealing their importance in the process of development of the Church as an institution in the 4th and 5th centuries. References:Primary Sources:Augustine, Collatio cum Maximino Arianorum episcopo. – In: Sancti Aurelii Avgvstini contra Arrianos opera, ed. Pierre Marie Hombert. [Corpus Christianorum Series Latina 87А] (Brepols, 2009), 383 – 470.Augustinus, SermoArrianorum =Antiarianische Schriften: Contra sermonem Arrianorum. Collatio cum Maximino Arrianorum episcopo. Contra Maximinum Arrianum. – In: Augustinus Werke, ed. and tr. Hermann Josef Sieben. [Zweisprachige Ausgabe 48 H] (Paderborn, 2008).Augustine of Hippo, Contra Maximinum Haereticum Arianorum Episcopum. – In: Patrologia Latina, ed. Jaques-Paul Migne, 42] (Paris, 1886), 743 – 814.Augustine, Arianism and Other Heresies intr., transl. and notes Roland Teske, ed. John E. Rotelle [The Works of Saint Augustine, vol. 18] (New York, 1995).Dissertatio Maximini contra Ambrosium – In: Kauffmann, F. (tr.), Aus der Schule de Wulfila, Texte und Untersuchungen zur altegermanidchen Religiousgeschichte. Texte 1 (Strasburg, 1899).Scolies Ariennes sur le concile d’Aquilée, ed. R. Gryson [Sources chrétiennes 267] (Paris, 1980), 237 – 251.The Theodosian Code and Novels and the Sirmondian Constitutions. Transl., comment., glossary, bibl. Clyde Pharr (Princeton University Press, 1952)Secondary Sources:Gerdzhikova 2022: Gerdzhikova, Zlatomira. The Arian Bishops from the Balkans. – Bulletin “Heritage BG” – Research announcements, ed. Emmanuel Moutafov, No. 3, 66 – 73.Gerdzhikova 2022: Gerdzhikova, Zlatomira. alladius of Ratiaria – the Arian voice from the Balkans. In: Voices and images from the Balkans. Forms of communication in the Medieval Balkans (4th – 16th c.) (ed. Lyubomir Maksimovich). Beograd, 19 – 41.Barnes 2023: Barnes, Michel. Augustine and Nicene Theology. Essays on Augustine and the Latin Argument for Nicaed. Eugene, OR.Barnes 1995: Barnes, Michel. Augustine in Contemporary Trinitarian Theology. – Theological Studies, No. 56, 237 – 250.Bonner 1963: Bonner, Gerald. St. Augustine of Hippo: Life and Controversies. Philadelphia Westminister Press.Bardenhewer 1962: Bardenhewer, Otto. Geschichte der Altkirchlichen Literatur, vol. 4. Parmstadt.Courcelle 1965: Courcelle, PierrePaul.Histoire littéraire grandes invasion germaniques. Paris.Gerber 2012: Gerber, Chad Tyler. The Spirit of Augustine’s Spirit Theolog. Conceptualizing Augustine’s Pneumatology. London.MacLynn 1996: MacLynn, Neil. From Palladius to Maximinus: Passing the Arian Torch. – Journal of Early Christian Studies, No. 4, 477 – 493.Mathisen 1999: Mathisen, Ralph W. Sigisvult the Patrician, Maximinus the Arian, and Political Stratagems in the Western Roman Empire ca. 425 – 440. – Early Medieval Europe, No. 8/2, 173 – 196.Mathisen 2004: Mathisen, Ralph W. Priests, Bishops, and Monks: Military Chaplains in the Roman Empire. In: The Sword of the Lord. Military Chaplains from the First to the Twenty-First Century (ed. Doris L. Bergen). Notre Dame, 3 – 28.Mathisen 2014: Mathisen, Ralph W. Barbarian ‘Arian’ clergy, church organization, and church practicesin. In: Arianism: Roman Heresy and Barbarian Creed (eds. G. Berndt, R. Steinacher). Ashgate, 145 – 192.Meslin 1967: Meslin, Michel. Les Ariens d’Occident: Paris, 335 – 430.Nuffelen 2011: Nuffelen, Peter Van. The Rhetoric of Rules and the Rule of Consensus. In: Episcopal elections in Late Antiquity (eds. J. Leemans, P.v. Nuffelen, Sh.W.J. Keough, C. Nicolaye). DeGruyter, 243 – 258.Parvis 2020: Parvis, Paul. Whistling in the Exegetical Dark: The Latin Pseudo-Origen Commentary on Job. – Studia Patristica, No. 100, 237 – 246. Revillout 1850: Revillout, Charles Jules. De l’arianisme des peoples germaniques qui evahi l’empire Romain. Paris.Sumruld 1994: Sumruld, William. Augustine and the Arians. The Bishop of Hippo’s Encounters with Ulfilian Arianism. Associated University Press, London and Toronto.Thompson 1966: Thompson, Ernest A. The Visigoths in the time of Ulfila. Oxford Clarendon Press. Teske 2009: Teske, Ronald. Augustine of Hippo: Philosopher, Exegete, and Theologian. A Second Collection of Esseys. Marquette University Press.Whelon 2018: Whelan, Robin. Being Christian in Vandal Africa. The Politics of Orthodoxy in the Post-Imperial West. Oukland.Zeiller 1918: Zeiller, Jacques. Les origines chrétiennes dans les provinces danubiennes de l’Empire romain. Paris
Keywords: Late Antiquity; Balkans; Arianism